Multi-Method Complex Approach for Hydration Assessment Does Not Detect a Hydration Difference in Hemodialysis versus Peritoneal Dialysis Patient - Anna Adamska-Wełnicka; Marcin Wełnicki; Paweł Krzesiński; Stanisław Niemczyk; Arkadiusz Lubas (Diagnostics, 2020)
Assessment of hydration status is essential in monitoring the effectiveness of renal replacement therapy and is usually based on physical examination. However, comparisons of hydration status achieved with different dialysis methods are not conclusive. We compared the hydration status of patients on chronic hemodialysis (HD, n = 60) and peritoneal dialysis (PD, n = 20) in a comprehensive assessment including physical examination and additional methods. The mean age of the 80 chronically dialyzed patients (53 males, 27 females) was 58.1 ± 13.9 years. The clinical evaluation took into account the presence of peripheral edema, dyspnea, and crackling over the lung fields. Additional tests included lung ultrasound, electrical bioimpedance (performed in 79 patients), impedance cardiography, ultrasound assessment of large abdominal vessels (performed in 79 patients), select echocardiographic parameters (obtained in 78 patients), and serum NT-proBNP concentration. Residual diuresis volume was significantly higher in the PD group. We found no significant differences between the two groups in any other baseline characteristics or in the results of the clinical examination or additional tests. The use of different methods for assessing hydration does not allow differentiation of patients treated with dialysis in terms of the dialysis technique used. Therefore, it seems reasonable to use common algorithms to objectify the hydration status of these patients.